THE INFLUENCE OF SHARIA BANKING CHARACTERISTICS AND MACROECONOMICS FACTORS ON SHARIA BANKING PROFITABILITY: EMPIRICAL STUDIES IN INDONESIA - Rofiqo, Azidni; Afrianti, Noni (UNISSULA, 2019)
The problem in this research is the unimmunity of teacher performance of SD Negeri in Mejobo District Kudus Regency. The purpose of this study is to analyze and to know the influence of Islamic Leadership on Teacher Performance through Teacher Competence and Quality of Work Life of Elementary School Teachers. The population of this research is all elementary school teachers from 3 villages in Mejobo District Kudus Regency as many as 129 people. This study used 100 teachers as a sample with Purposive Random Sampling. Datas were obtained from questionnaires and interviews. Data analysis using SPSS 16.0 and Eviews 9. The result of this research is Islamic Leadership, Teacher Competence, and Quality of Work Life positively influence to Teacher Performance. Based on data analysis only Quality of Work Life on Teacher Performance which has no significant effect. Teacher competence and Quality of Work Life can not be considered as intervening variable in this research.